EFFECTS OF THE GENRE-BASED WRITING INSTRUCTIONAL MODULE IN A BLENDED LEARNING ENVIRONMENT - Visser, Patricia; Sukavatee, Pornpimol (Journal of Education and Innovation, 2020)
Writing is considered as a challenging skill for Thai EFL university students. To overcome this challenge, integration of a genre-based approach into a blended learning environment has been considered as an alternative teaching approach to facilitate the students’ authentic and interactive writing development. This study employed a genre-based writing instructional module in a blended learning environment (GWIMBLE) to enhance the Thai learners’ English writing ability. The researchers designed 12 weeks of lesson plans, including procedural, descriptive, narrative, and persuasive genres. The sample of the study was 35 Thai EFL university students. Single-group experimental research was conducted using a pre-test and post-test. The results of the independent samples t-test revealed the positive effects of the GWIMBLE on the writing skills in the four genres focused on, and the quantitative data resulting from the attitude questionnaire and the qualitative data from the focus group interview indicated their satisfaction as well as their sense of achievement.